Patient‐reported experience of bleeding events in haemophilia. (June 2014) - Flood, Emuella; Pocoski, Jennifer; Michaels, Lisa A.; McCoy, Anne; Beusterien, Kathleen; Sasanè, Rahul
Abstract: Background: Patients with haemophilia experience bleeds because of absent or reduced clotting factor. The study objective was to understand the bleeding experience from the patients' perspective. Materials and methods: Individuals with moderate/severe haemophilia participated in interviews and were asked to describe their most recent bleeding experience, including symptoms, signs of onset, impacts, when bleeding stopped and treatment effectiveness. Interview transcripts were analysed using a thematic analysis involving the coding of transcripts to identify key concepts and themes. Results: Twenty males [10 adults, mean age = 41 (19–52); 10 adolescents, mean age = 13 (12–17)] with moderate ( n  = 5) or severe ( n  = 15) haemophilia participated. Symptoms signalling bleed onset included pain, swelling, stiffness, tingling/numbness and/or warmth. Participants reported feeling anger and frustration due to the unpredictable nature, pain and inconvenience of the episode. Adults sometimes reported delaying treatment due to inconvenience or cost; adolescents generally treated right away. Reported bleed severity was influenced by pain level, speed of symptom progression, location, continued use of the affected area, recurrence in same location of recent bleed and treatment delay. Participants reported that it was ' easy ' to know when the bleed had stopped. Participants reported that symptoms might linger for days before they returned back to ' normal '. Conclusions: This qualitative study details the substantial impact of an acute bleed from the patient perspective. Given that treatment was reported to be delayed in part due to inconvenience, more convenient treatment options could help reduce delays in treating bleeds and thereby minimise bleed‐related impacts. Clinical studies in haemophilia should include validated patient‐reported measurements of acute symptoms and bleed severity to comprehensively assess the bleeding event.